PENGELOLAAN MASJID AGUNG MADANI NASIONAL ISLAMIC CENTRE PASIR PENGARAIAN KABUPATEN ROKAN HULU - ", Nurmayani; Sadad, Abdul (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
The mosque is the first Muslim madrasah. Masjid Agung Madani NationalIslamic Center of Pasir Pengaraian Rokan Hulu regency is a mosque designated as anational pilot grand mosque and become a tourist destination in Rokan Hulu regency.This determination causes the mosque is widely known by people who want to knowabout this mosque. Based on observations in the field, the problem that occur is theneed for the management of this magnificent building, the addition of facilities andinfrastructure supporting activities in the face of busy visitors, as well as the placementof the board according to the field of expertise. The purpose of this study is to analyzethe management of the Masjid Agung Madani National Islamic Center of PasirPengaraian Rokan Hulu regency and its inhibiting factor. The concept of theory ismanagement revealed by Prajudi Atmosudirjo. This research uses qualitative researchmethod by studying data descriptively. Sources of data used are primary data andsecondary data. Data collection using interview technique, observation anddocumentation. Interviews were conducted with key informants as a source ofinformation and triangulation techniques as a source in testing the validity of data. Theresults of this study indicate that the management of the Masjid Agung Madani NationalIslamic Center of Pasir Pengaraian Rokan Hulu Regency is not effective. This isevidenced by the planning, organizing, directing and controlling in the operation of theprogram implementation activities constrained by the budget. The factors that inhibitthe budget constraints of funds, human resources, facilities and infrastructure supportand management right.Keywords: Management, Great Mosque, Tourist Attraction